(3QSGdI aj MaX GdUMIs - (3ehSi Hf YHjO Gddg Hf ejehf GdbQWHj, CHh YeQGf,J (B601 (3g` s
(3ChdgG (B:s
(3hQO Ydi Gdeedhc GdCUZQ ehSi Hf YHOj Gddg GdCeQ GdYGdi HCeQg HPcQ JOHjQ jYJeO Ydjg ai TaGA CeQGV YQVJ dehdGfG LYd Gddg GdCSbGe eLGfjI debQg GdYGdi s
(3BNQgG (B:s
(3hMeGQ GdhMTi dg NGUjI YXjeI ai JbhjI GdHUQ UM Pdc HGdJLQHI hGdcHGH GdYjf Ydi HNGQ WHjN dMeOI jbhi GdHUQ JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdJGSYIs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs